Distribution and Preference of Selected Dairy Breeds among Farmers of Bihar: A Socio-economic Analysis - Kumar, Abhinandan; Chandel, B S; Dixit, A K; Tiwari, Saurabh; Haritha, K; Kumar, Mandeep (Indian Journal of Extension Education, 2023)
The preference for dairy breeds is likely to depend on resource availability. This study attempted to analyze the distribution of the selected breeds of dairy animals among the farm size category, education, and experience of the dairy farmers. The study was conducted in the central region of Bihar and primary data was collected from January March 2021, from 70 farmers in respect of the selected dairy animals using a pre structured interview schedule. Ease of rearing index was developed and the preference of the dairy farmers towards the selected dairy breeds was estimated. The key findings revealed that 55 per cent of farmers were marginal farmers and mostly preferred indigenous breeds like Graded Sahiwal and Graded Murrah. The farmers rearing Graded Sahiwal (67%) and Graded Murrah (69%) were having qualifications up to secondary education. Highly experienced farmers were rearing buffalo whereas Graded Sahiwal (67%) and crossbred (72%) animals were kept by farmers having experience less than or equal to 20 years. The ease of rearing index revealed that most of the farmers were preferring indigenous breed to rear because of its qualitative parameters. It can be concluded that farmers are having likeness towards indigenous breeds which needs to be promoted.
Keywords: Breeds; Ease of rearing index; Farmers; Graded Sahiwal; Preference; Qualitative